2009
DOI: 10.1364/oe.17.012588
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal bleaching of photodarkened Yb-doped fibers

Abstract: We report on the thermal treatment of photodarkened Yb-doped fiber samples. The method of non-isothermal bleaching at different temperature ramp rates can be used to determine the thermal energy distribution of photodarkening induced color centers. A distributed activation energy with a mean value of about 1.3 eV and a FWHM of 0.5 eV was found. Spectral changes during thermal treatment were observed and could be interpreted, e.g. as an enhancement of the absorption cross section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 10 publications
2
29
0
Order By: Relevance
“…The kinetic analysis of this glow peak indicated that the thermal activation energy of the related trapped-hole center is about 1.3 eV. This estimate is in fair agreement with activation energies obtained by other methods for the thermal bleaching of PD, namely 1.3 eV [18] and 1.26-1.50 eV [19]. In view of these values, the PI of trapped holes should be most efficiently achieved by photons around 2.5 eV (or more).…”
Section: Modelsupporting
confidence: 88%
See 1 more Smart Citation
“…The kinetic analysis of this glow peak indicated that the thermal activation energy of the related trapped-hole center is about 1.3 eV. This estimate is in fair agreement with activation energies obtained by other methods for the thermal bleaching of PD, namely 1.3 eV [18] and 1.26-1.50 eV [19]. In view of these values, the PI of trapped holes should be most efficiently achieved by photons around 2.5 eV (or more).…”
Section: Modelsupporting
confidence: 88%
“…Then, trapped-hole states responsible for the induced optical loss, i.e. acting as color centers, may spread from at least ∼1.27 eV (980 nm) above the VB (consistent with [18,19]). Based on these hypotheses, we propose to describe PD, RD and PRD by the model of Fig.…”
Section: Modelmentioning
confidence: 98%
“…This opens for the possibility to directly relate observed change in absorption with activation energy. For pre-darkened fibers an unexpected increase in PD absorption is hereby observed for annealing ramps from room temperature to about 350-450 K followed by the expected bleaching that initiate at 470-600 K [11,12]. Thermally induced PD absorption is not observed for pristine fibers [12] while PD bleaching shows E A of ≈1.3 eV [12,13] to 1.5 eV [13] dependent on fiber composition and manufacturing condition.…”
Section: +mentioning
confidence: 64%
“…The interpolated bond energies found hereby are along with Bose-Einstein phonon statistics applied to develop a Markov chain statistical model for annealing of pre-darkened fibers. This model gives good match to the annealing data from [11][12][13] for a distributed set of CC sites of individual TEB polarization.…”
Section: +mentioning
confidence: 71%
See 1 more Smart Citation